2015
DOI: 10.1002/psc.2826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distal sugar and interglycosidic linkage of disaccharides on the activity of proline rich antimicrobial glycopeptides

Abstract: The effect of glycosylation on protein structure and function depends on a variety of intrinsic factors including glycan chain length. We have analyzed the effect of distal sugar and interglycosidic linkage of disaccharides on the properties of proline-rich antimicrobial glycopeptides, formaecin I and drosocin. Their glycosylated analogs-bearing lactose, maltose and cellobiose, as a glycan side chain on their conserved threonine residue, were synthesized where these disaccharides possess identical proximal sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
(48 reference statements)
4
12
0
Order By: Relevance
“…Having established the mechanism of Dro action, we proceeded to define the structural features of this PrAMP critical for its ability to inhibit translation termination. Previous efforts to improve the antibiotic activity of Dro involved introduction of specific amino acid changes in its structure 33,45,46 . Some of these alterations indeed yielded derivatives with somewhat improved antibacterial properties or serum stability 45,47-49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having established the mechanism of Dro action, we proceeded to define the structural features of this PrAMP critical for its ability to inhibit translation termination. Previous efforts to improve the antibiotic activity of Dro involved introduction of specific amino acid changes in its structure 33,45,46 . Some of these alterations indeed yielded derivatives with somewhat improved antibacterial properties or serum stability 45,47-49 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous efforts to improve the antibiotic activity of Dro involved introduction of specific amino acid changes in its structure 33,45,46 . Some of these alterations indeed yielded derivatives with somewhat improved antibacterial properties or serum stability 45,[47][48][49] .…”
Section: Endogenously Expressed Dro Retains Its Mechanism Of Action A...mentioning
confidence: 99%
“…1b). In addition, we examined the previously reported (Lele et al, 2015a;Talat et al, 2011) drosocin derivatives bearing b-D-…”
Section: Sbma Plays a Major Role In Drosocin Uptakementioning
confidence: 99%
“…Synthetic drosocin lacking O-glycosylation is less active than the native compounds, suggesting that the post-translational modification is necessary for full activity (Bulet et al, 1993; Bulet et al, 1999; Bulet et al, 1996; Gobbo et al, 2002; Hoffmann et al, 1999). Indeed, many studies have demonstrated that a variety of synthetic drosocin derivatives with varying sugar moieties maintain good antimicrobial activity, generally better than the unmodified form (Ahn et al, 2011a; Ahn et al, 2011b; Gobbo et al, 2002; Lele et al, 2015a; Marcaurelle et al, 1998; Otvos et al, 2000; Rodriguez et al, 1997; Talat et al, 2011). Although NMR and CD experiments suggest that both the modified and unmodified forms of drosocin adopt extended conformations in solution (Bulet et al, 1996; Gobbo et al, 2002; Lele et al, 2015a; McManus et al, 1999; Talat et al, 2011), the presence of the modification has nevertheless been proposed to help drosocin maintain an extended conformation to facilitate binding to its intracellular target (Bulet et al, 1999; Gobbo et al, 2002; McManus et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation